The Impact of Kurdish Religious Discourse in Strengthening National Identity: A Study of Sheikh Mohammed Khal's Works - ساڵح, د.مه‌جيد (Sulaimani Journal for Humanities, 2023)
This study examines the role of religious discourse written in Kurdish in enhancing Kurdish national identity, focusing on the works of Sheikh Mohammed Khal. It explores the intersection of religion and nationalism in the Kurdish context, where religious writings have served as a powerful tool in preserving the cultural and national identity of the Kurdish people, particularly during periods of oppression and attempts to erase Kurdish identity. Through an analysis of Sheikh Mohammed Khal's books, the study investigates how he successfully employed religion as a bridge to strengthen national unity and a sense of belonging. It highlights the significance of his use of the Kurdish language in religious writings as a means of communicating with the Kurdish people in their mother tongue, which contributed to the preservation of Kurdish language and culture. The study also discusses the intellectual dimensions of religious discourse in reinforcing national identity, showing how religious principles were integrated with national values to foster unity and resistance against cultural erasure. The study concludes that Kurdish religious discourse, through the writings of Sheikh Mohammed Khal, played a significant role in supporting and strengthening Kurdish national identity, becoming an essential part of the cultural and political struggle to maintain the uniqueness of the Kurdish nation.
Keywords: Religious discourse; national identity; Kurdish religious books; nationalism